Kualitas dan Daya Tahan Produk Makeup Brand Lokal untuk Rias Pengantin Internasional: Analisis Perkembangan dan Tantangan - Anik Maghfiroh; Ifa Nurhayati; One Juniar Putri Pratama; Darul Falaqis Salaf; Rahel Tio Srilinsky Hutagaol; Salsa Kesya Anugraheni (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to examine the quality and durability of local Indonesian makeup brands in the context of international bridal makeup. The research method used is a literature review, collecting and analyzing various related publications regarding local makeup products, especially concerning product durability and quality under extreme conditions. The findings indicate that local Indonesian makeup products, such as Wardah, Make Over, Emina, and others, have shown competitive quality and can withstand extreme conditions, although challenges remain, such as consistency between batches and performance outdoors. Despite these challenges, the use of local products in international bridal makeup is increasingly accepted due to continuous innovations.